Diplomasi Akademik Pendidikan Islam di Asia Tenggara Melalui Forum Seminar Internasional di Fatoni University Thailand - Fahri Hidayat; M. Slamet Yahya; Muhamatsakree Manyunu; Jayanti Syahfitri; Nurhawatee Sulongsen (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2026)
This community service program (PkM) aims to strengthen academic capacity and build international networks in the development of Islamic education in Southeast Asia, particularly between Indonesia and Southern Thailand. The target participants are the academic community at Fatoni University, engaged through an international seminar as a medium for knowledge dissemination and the exchange of best practices. The method employed is a participatory, collaborative, and educational approach, implemented through academic lectures, interactive discussions, and question-and-answer sessions. The results indicate an increased understanding among participants of the dynamics of Islamic education, particularly in integrating tradition and modernity. In addition, the program has generated academic collaboration, marked by the signing of a memorandum of understanding (MoU), opportunities for joint research, and the strengthening of regional intellectual networks. This PkM contributes to reinforcing academic diplomacy as a strategic approach to the development of cross-border Islamic education.